Evaluating the role of time in range as a glycemic target during short‐term intensive insulin therapy in patients with newly diagnosed type 2 diabetes. Issue 2 (17th January 2023) - Liu, Liehua; Ke, Weijian; Xu, Lijuan; Li, Hai; Liu, Juan; Wan, Xuesi; Liu, Jianbin; Deng, Wanping; Cao, Xiaopei; Xiao, Haipeng; Li, Yanbing
Abstract: Background: Tight glycemic control during short‐term intensive insulin therapy (SIIT) is critical for inducing diabetes remission in patients with newly diagnosed type 2 diabetes (T2D). This work aimed to investigate the role of time in range (TIR) during SIIT as a novel glycemic target by predicting clinical outcomes. Methods: SIIT was given to 116 patients with newly diagnosed T2D, with daily eight‐point capillary glucose monitored. Glycemic targets (fasting/premeal glucose, 3.9–6.0 mmol/L; 2 h postprandial blood glucose, 3.9–7.8 mmol/L) were achieved and maintained for 2 weeks. TIRPIR was calculated as the percentage of glucose points within these glycemic targets during the maintenance period and was compared to TIR3.9–7.8mmol/L and TIR3.9–10.0mmol/L . Acute insulin response (AIR), HOMA‐IR, HOMA‐B, and disposition index (DI) were measured. Patients were followed up for 1 year to observe clinical outcomes. Results: TIRPIR, TIR3.9–7.8mmol/L, and TIR3.9–10.0mmol/L were 67.2 ± 11.2%, 80.8 ± 9.2%, and 90.1 ± 6.2%, respectively. After SIIT, β‐cell function and insulin sensitivity improved remarkably, and the 1‐year remission rate was 55.2%. △AIR and △DI were positively correlated with all the TIR values, whereas only TIRPIR was correlated with △HOMA‐IR (r = −0.22, p = 0.03). Higher TIRPIR but not TIR3.9–7.8mmol/L or TIR3.9–10.0mmol/L was robustly associated with diabetes remission; patients in the lower TIRPIR tertile had an elevated risk of hyperglycemia relapse (hazard ratio 3.4, 95% confidence interval 1.6–7.2， p = .001). Only those with TIRPIR ≥ 65% had a one‐year remission rate of over 60%. Conclusions: These findings advocate TIRPIR ≥ 65% as a novel glycemic target during SIIT for clinical decision‐making. Abstract : Highlights Whether time in range (TIR) during short‐term intensive insulin therapy (SIIT) was associated with treatment response to the therapy in patients with newly diagnosed type 2 diabetes was uncertain. TIRPIR, which was calculated according to the percentage of glucose points within predefined glycemic targets, was superior to TIR3.9–7.8mmol/L, TIR3.9–10.0mmol/L, and other glycemic markers in predicting recovery of β‐cell function, improvement of insulin sensitivity, and 1‐year remission. Patients with TIRPIR ≥ 65% had a 1‐year remission rate of 60% or higher. 摘要: 背景: 短期强化胰岛素治疗(SIIT)期间的严格血糖控制对新诊断2型糖尿病(T2D)患者的糖尿病缓解至关重要。本研究旨在探讨SIIT期间葡萄糖目标范围内时间(TIR)作为预测临床结局的新型血糖目标的作用。 方法: 对116例新诊断的T2D患者进行SIIT治疗, 每日监测8‐点毛细血管血糖。血糖控制达标(空腹/餐前血糖, 3.9 6.0 mmol/L;餐后2h血糖3.9 7.8mmol/L), 并维持2周。TIRPIR 计算为维持期这些血糖目标内的血糖点百分比, 并与TIR3.9‐7.8mmol/L 和TIR3.9‐10.0mmol/L 进行比较。测定急性胰岛素反应(AIR)、(HOMA‐IR、HOMA‐B和葡萄糖处置指数(DI)。随访患者1年, 观察临床疗效。 结果: TIRPIR 、TIR3.9 7.8mmol/L 和TIR3.9 10.0mmol/L 分别为67.2±11.2%、80.8±9.2%和90.1±6.2%。SIIT后患者胰岛β细胞功能及胰岛素敏感性明显改善, 1年缓解率为55.2%。△AIR、△DI与所有TIR值均呈正相关, 仅TIRPIR 与△HOMA‐IR呈正相关(r=‐0.22, P=0.03)。较高的TIRPIR 与糖尿病缓解密切相关, 而TIR3.9‐7.8mmol/L 或TIR3.9‐10.0mmol/L 与糖尿病缓解无关, 低TIRPIR 三分位组患者高血糖复发风险增加(HR 3.4, 95%CI 1.6 7.2, P=0.001)。只有TIRPIR ≥65%的患者1年缓解率超过60%。 结论: 建议将TIRPIR ≥65%作为SIIT期间新的血糖控制目标, 以指导临床决策。